Evaluation of a Novel Multidisciplinary Preoperative Workup Strategy for Geriatric Hip Fractures. Issue 8 (August 2022) - Steffensmeier, Andrew; Hoge, Connor; Shah, Nihar; Matar, Robert; Rice, Morgan; Grawe, Erin; Held, Justin; Budde, Bradley; Laughlin, Richard; Sagi, H. Claude
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To determine the financial and clinical impact of a standardized, multidisciplinary team for surgical clearance and optimization in geriatric hip fracture patients. Design: Retrospective case series. Setting: Level-1 trauma center. Patients: One hundred twenty-four geriatric patients (age >65 years old) in the preprotocol group (cohort 1; January 2017–December 2018) and 98 geriatric patients in the postprotocol group (cohort 2; October 2019–January 2021) with operative hip fractures. Intervention: Implementation of a multidisciplinary team protocol consisting of Anesthesiology, Internal Medicine and Orthopedic Surgery departments for the assessment of medical readiness and optimization for surgical intervention in geriatric hip fractures. Main Outcome Measures: Rate of cardiology consultation, need for cardiac workup (echocardiography stress testing, heath catheterization), time to medical readiness (TTMR), time to surgery, case-cancellation rate, length of stay (LOS), and total hospitalization charges. Results: Following implementation of the new protocol, there were significant ( P < 0.001) decreases in TTMR (19 vs. 11 hours), LOS (149 vs. 120 hours), case cancellation rate, and total hospital charges (84, 000 vs. 62, 000). There were no significant differences with respect to in-hospital complications or readmission rates/mortality rates at 1 year. Conclusions: Following implementation of a protocolized, multidisciplinary approach to optimizing geriatric fracture patients, we were able to demonstrate a reduction in unnecessary preoperative testing, TTMR for surgery, case cancellation rate, LOS, and total hospitalization charge—without a concomitant increase in complications or mortality. This study highlights that standardization of the perioperative care for geriatric hip fracture patients can provide effective patient care while also lowering financial and logistical burden in care for these injuries. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.